Positioning Informal Skills Learners in TVET System of Nepal - Baral, Durga Prasad (Journal of Education and Research, 2020)
The informal sector occupies a significant portion of employment in Nepal. More than eighty per cent of all employees work in this sector. These workers generally lack formal skills training and acquire skills while performing the work under the guidance of skilled workers. However, the technical and vocational education and training (TVET) system rarely recognises such informally learned skills at work. In this context, this paper explores the position obtained by informal skills learners in the existing TVET system of Nepal. I drew information from related literature, collected experiences of six informal skills learners as cases and incorporated views of eight experts through interviews. The study shows that informal skills learners are getting very little attention in the Nepali TVET system. In fact, the system is not valuing the contribution of local communities and institutions, industries, and enterprises in the development of skills. Furthermore, the study reveals that lacking awareness-raising and motivational programmes targeted to youth; and the government‘s unfavourable working approach to TVET. In this situation, I argue that obtaining a dignified position by informal skills learners depends on the value given to skills, work, and occupation. The paper concludes that Pervasive Loitering Syndrome (PLS) prevails across different layers of society. The PLS creates the situation of less valuing skills, work, and occupations, and ultimately the informal skills learners are devalued.